Conformational changes in CLIP-170 regulate its binding to microtubules and dynactin localization - Lansbergen, Gideon (The Rockefeller University Press, 2004)
Cytoplasmic linker protein (CLIP)-170, CLIP-115, and the dynactin subunit p150(Glued) are structurally related proteins, which associate specifically with the ends of growing microtubules (MTs). Here, we show that down-regulation of CLIP-170 by RNA interference results in a strongly reduced accumulation of dynactin at the MT tips. The NH(2) terminus of p150(Glued) binds directly to the COOH terminus of CLIP-170 through its second metal-binding motif. p150(Glued) and LIS1, a dynein-associating protein, compete for the interaction with the CLIP-170 COOH terminus, suggesting that LIS1 can act to release dynactin from the MT tips. We also show that the NH(2)-terminal part of CLIP-170 itself associates with the CLIP-170 COOH terminus through its first metal-binding motif. By using scanning force microscopy and fluorescence resonance energy transfer-based experiments we provide evidence for an intramolecular interaction between the NH(2) and COOH termini of CLIP-170. This interaction interferes with the binding of the CLIP-170 to MTs. We propose that conformational changes in CLIP-170 are important for binding to dynactin, LIS1, and the MT tips.